X-ray fluorescence data from Contessa Road (Italy), Paleocene-Eocene Thermal Maximum interval - Piedrahita, Victor A; Galeotti, Simone; Zhao, Xiang; Roberts, Andrew P; Rohling, Eelco J; Heslop, David; Florindo, Fabio; Grant, Katharine M; Rodriguez-Sanz, Laura; Reghellin, Daniele; Zeebe, Richard E (PANGAEA, 2023)
The Paleocene-Eocene Thermal Maximum (PETM) is the most studied global warming event of a series of Paleocene-Eocene carbon cycle perturbations called hyperthermals. PETM origins have been associated with volcanic-related carbon emissions; however, other carbon cycle feedbacks were required to develop a large hyperthermal such as the PETM. The orbital configuration in which the PETM occurred is still unclear despite possible orbital controls on the PETM triggering. This dataset contains X-Ray Fluorescence (XRF) data (Fe, Ca, and Si) from Contessa Road (Italy), a sedimentary section with reduced calcium carbonate dissolution compared to deep ocean sites. Astrochronological age models and probabilistic assessments reveal that the PETM onset appeared close to both short and long eccentricity maxima, which suggests that orbitally controlled insolation variations may have thermally destabilized carbon reservoirs that worked as PETM positive carbon cycle feedbacks.
Keywords: CaCO3 dissolution; long eccentricity maximum; orbital control; Paleocene-Eocene Thermal Maximum (PETM); short eccentricity maximum